Attacking the double burden of malnutrition in Asia and the Pacific - Gillespie, Stuart; Haddad, Lawrence J. (Asian Development Bank, 2001)
This work was carried out as part of the ADB-IFPRI Regional Technical Assistance Project on Nutrition Trends, Policies and Strategies in Asia and the Pacific. Malnutrition’s causes and solutions at each stage of the human life cycle are discussed in a regional study on Nutrition Trends, Policies and Strategies and synthesized in this publication. The study aims to create a better understanding of ways to improve life span, quality of life, early cognition and life-long learning, and earning capacity of individuals and nations.